Peripheral Surgical Wounding and Age-Dependent Neuroinflammation in Mice - Xu, Zhipeng (Public Library of Science, 2014)
Post-operative cognitive dysfunction is associated with morbidity and mortality. However, its neuropathogenesis remains largely to be determined. Neuroinflammation and accumulation of β-amyloid (Aβ) have been reported to contribute to cognitive dysfunction in humans and cognitive impairment in animals. Our recent studies have established a pre-clinical model in mice, and have found that the peripheral surgical wounding without the influence of general anesthesia induces an age-dependent Aβ accumulation and cognitive impairment in mice. We therefore set out to assess the effects of peripheral surgical wounding, in the absence of general anesthesia, on neuroinflammation in mice with different ages. Abdominal surgery under local anesthesia was established in 9 and 18 month-old mice. The levels of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), Iba1 positive cells (the marker of microglia activation), CD33, and cognitive function in mice were determined. The peripheral surgical wounding increased the levels of TNF-α, IL-6, and Iba1 positive cells in the hippocampus of both 9 and 18 month-old mice, and age potentiated these effects. The peripheral surgical wounding increased the levels of CD33 in the hippocampus of 18, but not 9, month-old mice. Finally, anti-inflammatory drug ibuprofen ameliorated the peripheral surgical wounding-induced cognitive impairment in 18 month-old mice. These data suggested that the peripheral surgical wounding could induce an age-dependent neuroinflammation and elevation of CD33 levels in the hippocampus of mice, which could lead to cognitive impairment in aged mice. Pending further studies, anti-inflammatory therapies may reduce the risk of postoperative cognitive dysfunction in elderly patients.